Multicenter study on postcardiotomy venoarterial extracorporeal membrane oxygenation - Biancari, Fausto; Dalén, Magnus; Fiore, Antonio; Ruggieri, Vito G; Saeed, Diyar; Jónsson, Kristján; Gatti, Giuseppe; Zipfel, Svante; Perrotti, Andrea; Bounader, Karl; Loforte, Antonio; Lechiancole, Andrea; et al. (The Journal of thoracic and cardiovascular surgery, 2020)
OBJECTIVES: The aim of this study was to identify the risk factors associated with early mortality after postcardiotomy venoarterial extracorporeal membrane oxygenation. METHODS: This is an analysis of the postcardiotomy extracorporeal membrane oxygenation registry, a retrospective multicenter cohort study including 781 patients aged more than 18 years who required venoarterial extracorporeal membrane oxygenation for cardiopulmonary failure after cardiac surgery from 2010 to 2018 at 19 cardiac surgery centers. RESULTS: After a mean venoarterial extracorporeal membrane oxygenation therapy of 6.9 ± 6.2 days, hospital and 1-year mortality were 64.4% and 67.2%, respectively. Hospital mortality after venoarterial extracorporeal membrane oxygenation therapy for more than 7 days was 60.5% (P = .105). Centers that had treated more than 50 patients with postcardiotomy venoarterial extracorporeal membrane oxygenation had a significantly lower hospital mortality than lower-volume centers (60.7% vs 70.7%, adjusted odds ratio, 0.58; 95% confidence interval, 0.41-0.82). The postcardiotomy extracorporeal membrane oxygenation score was derived by assigning a weighted integer to each independent pre-venoarterial extracorporeal membrane oxygenation predictors of hospital mortality as follows: female gender (1 point), advanced age (60-69 years, 2 points; ≥70 years, 4 points), prior cardiac surgery (1 point), arterial lactate 6.0 mmol/L or greater before venoarterial extracorporeal membrane oxygenation (2 points), aortic arch surgery (4 points), and preoperative stroke/unconsciousness (5 points). The hospital mortality rates according to the postcardiotomy extracorporeal membrane oxygenation score was 0 point, 45.6%; 1 point, 40.5%; 2 points, 51.1%; 3 points, 57.8%; 4 points, 70.7%; 5 points, 68.3%; 6 points, 77.5%; and 7 points or more, 89.7% (P < .0001). CONCLUSIONS: Age, female gender, prior cardiac surgery, preoperative acute neurologic events, aortic arch surgery, and increased arterial lactate were associated with increased risk of early mortality after postcardiotomy venoarterial extracorporeal membrane oxygenation. Center experience with postcardiotomy venoarterial extracorporeal membrane oxygenation may contribute to improved results.
Keywords: senioři; cardiac surgery; venoarterial; extracorporeal membrane oxygenation; Retrospective Studies; mimotělní membránová oxygenace; výsledek terapie; Middle Aged; mužské pohlaví; Cardiac Surgical Procedures; ženské pohlaví; retrospektivní studie; kardiochirurgické výkony; Extracorporeal Membrane Oxygenation; Hemodynamics; Humans; hemodynamika; lidé středního věku; postcardiotomy; rizikové faktory; Female; Aged; Risk Factors; Treatment Outcome; lidé; Male